Draft Five Year Plan 1978-83 Welfare of Prisoners Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
Only 2 schemes were included in the 5th Five Year plan of the State and expenditure as shown below has been incurred so far.
Government of Madhya Pradesh, Planning, Economics and Statistics Department